2011
DOI: 10.1007/s11010-011-1118-5
|View full text |Cite
|
Sign up to set email alerts
|

The calcium-sensing receptor promotes adipocyte differentiation and adipogenesis through PPARγ pathway

Abstract: Adipocyte differentiation and adipogenesis are closely related to obesity and obesity-induced metabolic disorders. The calcium-sensing receptor (CaSR) has been reported to play an antilipolytic role in human adipocyte and regulate cell differentiation in many tissues. However, the effects of CaSR on adipocyte differentiation and adipogenesis have not been clarified. In the study, we observed that activation of CaSR significantly promoted adipocyte differentiation and adipogenesis in human SW872 adipocytes. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…Coordinated up-regulation of PPARγ and cGPDH genes expression during adipocyte differentiation and adipogenesis was also recently reported [30]. Current data indicates that resveratrol [31] or kefir [32] coordinately decrease lipid accumulation, cGPDH activity, and PPARγ gene expression in 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 60%
“…Coordinated up-regulation of PPARγ and cGPDH genes expression during adipocyte differentiation and adipogenesis was also recently reported [30]. Current data indicates that resveratrol [31] or kefir [32] coordinately decrease lipid accumulation, cGPDH activity, and PPARγ gene expression in 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 60%
“…A study from Hu and colleagues demonstrated the molecular identities of calcium signaling pathways in human preadipocytes [2]. Further, in human adipocytes, increases in cytosolic calcium exhibited a biphasic effect (increase in cytosolic calcium inhibited the early stages but enhanced the late stage of differentiation) in the regulation of adipocyte differentiation [1,8]. Calcium activated downstream signaling in the cell includes both pro-and antiadipogenic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Other calcium‐binding factors like the G‐protein–coupled extracellular calcium‐sensing receptor (CaSR) (44) and calcineurin (45) have been associated with adipocyte differentiation. Activated CaSRs in response to changes in extracellular calcium concentration promotes adipocyte differentiation by increasing PPARγ and its downstream expressions of C/EBPα, aP2, and lipoprotein lipase.…”
Section: Discussionmentioning
confidence: 99%